Transcriptional and posttranscriptional regulation of the plasminogen activator system - Nagamine, Yoshikuni; Medcalf, Robert L.; Muñoz-Cánoves, Pura (Thrombosis and Haemostasis, 2005)
The core protein components of the plasminogen activator (PA) system are two plasminogen activators, two plasminogen activator inhibitors and a urokinase type plasminogen activator-specific cell surface receptor. Various types of biological regulation are exerted through the interplay of these components mutually and with extracellular matrix proteins and cell membrane proteins, with or without involving proteolytic activity. Reflecting these diverse biological roles, the level and activity of each component of the PA system is under the control of a variety of regulatory mechanisms. The expression level of a protein reflects the level of the corresponding mRNA, which is essentially the net result of de novo synthesis, i.e. transcription, and degradation. Many recent studies have shown that the regulation of mRNA stability is dynamic and cell specific. Accordingly, we are learning that the mRNAs of the PA system are also the subject of diverse regulatory mechanisms. In this short review, we summarize current understanding of the transcriptional and mRNA-stability regulation of the PA system.
Keywords: Review; plasminogen activator; gene regulation; mRNA stability